Mechanisms governing the fragmentation of glycerophospholipids containing choline and ethanolamine polar head groups. Issue 6 (December 2017) - Colsch, Benoit; Fenaille, François; Warnet, Anna; Junot, Christophe; Tabet, Jean-Claude
Glycerophospholipids are the major amphiphilic molecules found in the plasma membrane bilayer of all vertebrate cells. Involved in many biological processes, their huge structural diversity and large concentration scale make their thorough characterization extremely difficult in complex biological matrices. Mass spectrometry techniques are now recognized as being among the most powerful methods for the sensitive and comprehensive characterization of lipids. Depending on the experimental conditions used during electrospray ionization mass spectrometry experiments, glycerophospholipids can be detected as different molecular species (e.g. protonated, sodiated species) when analyzed either in positive or negative ionization modes or by direct introduction or hyphenated mass spectrometry-based methods. The observed ionized forms are characteristic of the corresponding phospholipid structures, and their formation is highly influenced by the polar head group. Although the fragmentation behavior of each phospholipid class has already been widely studied under low collision energy, there are no established rules based on charge-induced dissociation mechanisms for explaining the generation of fragment ions. In the present paper, we emphasize the crucial roles played by ion–dipole complexes and salt bridges within charge-induced dissociation processes. Under these conditions, we were able to readily explain almost all the fragment ions obtained under low-energy collision-induced dissociation for particular glycerophospholipids and lysoglycerophospholipids species including glycerophosphatidylcholines and glycerophosphatidylethanolamines. Thus, in addition to providing a basis for a better comprehension of phospholipid fragmentation processes, our work also highlighted some potentially new relevant diagnostic ions to signal the presence of particular lipid species.